Egypt: Revolution 2011/2025. Dystopia, Utopia, and Political Fiction in Mustafa Al-Husayni’s Novel "2025 An-Nida Al-Akhir" - Dziekan, Marek M. (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The article discusses the novel 2025. An-Nida al-Akhir [2025. The Last Call] written by a young Egyptian journalist and writer born in 1982 – Mustafa al-Husayni. The novel was published in early 2011, between the fall of Zayn al-Abidin Ibn Ali in Tunisia and of Husni Mubarak in Egypt. It describes a revolution against the regime of Jamal al-Mubarak, son of Husni, spurred by a group of young Egyptians. The story takes place in 2025 and anticipates the development of the political situation in Egypt and the Middle East between 2011 and 2025 in a utopian/dystopian manner. Alongside Utopia by Ahmad Khalid Tawfik and the poetry of Usama al-Abnubi and Abd ar-Rahman al-Abnudi, al-Husayni’s book is considered to be a forecast of the Arab Spring in Egypt.